Factors Associated With Unintended Pregnancy Outcome Among CHOICE Participants [243]. (May 2015) - Eisenberg, David L.; Lange, Julia; Zhao, Qiuhong; Madden, Tessa; Peipert, Jeffrey F.
Abstract : INTRODUCTION: Outcomes of unintended pregnancies are influenced by many factors. This study aims to assess factors associated with continuation or termination of unintended pregnancies that occur when no-cost contraception is available. METHODS: We performed a secondary analysis of data from the Contraceptive CHOICE Project (CHOICE), a prospective cohort study of 9, 256 reproductive-aged women provided with no-cost contraception. Women who experienced their first unintended pregnancy after CHOICE enrollment were included; those with ectopic pregnancies and spontaneous losses were excluded. Using univariate and multivariable analyses, we estimated correlates of pregnancy outcome using chi-square and Poisson regression. RESULTS: We identified 520 pregnancies that met inclusion criteria; 326 (62.7%) ended in live birth and 194 (37.3%) in induced abortion. Among women with pregnancy prior to CHOICE, 93% reported at least one unintended pregnancy. Pregnancy outcomes were not associated with race/ethnicity, educational/economic factors, or contraceptive method or compliance. Multivariable regression analysis demonstrated married/cohabiting women were more likely to continue a pregnancy (RRadj 1.22, 95% CI 1.07–1.41) than single/never married participants. Women ≥35 years old (RRadj 0.47, 95% CI 0.25–0.88) or with a previous abortion (RRadj 0.78, 95% CI 0.68–0.91) were less likely to continue their unintended pregnancy compared to teenagers and those without a prior induced abortion, respectively. CONCLUSION: The decision to continue or terminate a pregnancy in CHOICE was associated with partner status, age, and abortion history. Partnered women were more likely to continue an unintended pregnancy, whereas those with at least one prior abortion and in the oldest age group were more likely to terminate the pregnancy.